Effects of workplace spirituality and trust mediated by perceived risk towards knowledge sharing behaviour - Rahman, Muhammad Sabbir; Mat Daud, Nuraihan; Hassan, Hasliza; Osman-Gani, AAhad M. (Emerald, 2016)
This research paper aims to provide an empirical examination to explain the relationship between trust, workplace spirituality, perceived risk and knowledge sharing behaviour among the non-academic staff of private higher learning institutions.